Official development assistance, income per capita and health outcomes in developing countries: Is Africa different? - E. Chuke Nwude; Robinson O. Ugwoke; Peter Chinyere Uruakpa; Ugochukwu Sebastine Ugwuegbe; Nnenna G. Nwonye (Cogent Economics & Finance, 2020)
In this study, we investigate the effect of official development assistance and income per capita on health outcomes in developing countries. Health outcome is proxied by life expectancy and under-5-mortality rate. We accounted for the endogeneity problem in the model by employing a dynamic two-step system generalized method of moments (GMM) estimator. We find that official development assistance does not improve health outcome in developing countries, while income per capital significantly improves health outcome in developing countries. The study reports that CO2 emission is not a significant determinant of health outcome in developing countries but the prevalence of HIV and Immunization significantly determines health outcomes in developing countries. More specifically the prevalence of HIV increases the under-5-mortality rate and decreases life expectancy; immunization increases life expectancy but decreases under-5-mortality rate. It was equally revealed in the study that health outcome in Sub-Saharan Africa (SSA) does not significantly differ from health outcomes in other developing countries. We equally reported that the effect of income per capita on health outcome in Sub-Saharan Africa countries is not significantly different from that of non-SSA countries. The effect of official development assistant on health outcome in SSA was found to be significantly different from non-SSA countries. The study reveals that the effect of ODA on life expectancy in SSA is less compared to its effect on non-SSA countries. Similarly, the effect of ODA on under-5-mortality is higher in SSA countries as against other non-SSA countries.
Keywords: B22; F35; I15; P45; 330; life expectancy; official development assistance and income per capita; under-5-mortality rate